Development of Encyclopedia Based on Ethnogastronomy of Sambas Malay Porridge - Dita Aulianti; Sunandar Ari; Hanum Mukti Rahayu (Postgraduate, University of Mataram, 2024)
Biology learning is essentially learning that always relates science to the environment and living things. Therefore, there is a need for learning media that contains local wisdom related to the surrounding environment. This study aims to determine the validity of the ethnogastronomy-based encyclopedia of Sambas Malay porridge and to determine student responses to the ethnogastronomy-based encyclopedia of Sambas Malay porridge. The research method used is R&D, in this study a 4-D development model is used, namely the define, design, development and disseminate stages, but in this development the researcher only reaches the development stage. This research was conducted on students of class X SMAN 1 Tekarang. The research instrument used was a questionnaire to obtain product validation and determine student responses to the developed product. Product validation was carried out by material experts, linguists, media experts, and student responses. The results showed that the encyclopedia developed was considered valid. The results of the material expert validator assessment were 93.81% (very valid), language experts were 86.67% (very valid), media experts were 95.00% (very valid). Student responses were obtained through 2 stages, namely small-scale trials of 72.58% (positive) and large-scale trials of 90.00% (very positive). Overall, it can be concluded that the encyclopedia developed is valid and gets a positive response from students.